Influence of passively acquired colostral immunity on neonatal lamb mortality in Ethiopian highland sheep - Tekelye Bekele; Otesile, E.B.; Kasali, O.B. (Elsevier, 1992)
Presents a study performed to determine the level of serum immunoglobulins (Ig) and efficiency of passive immune transfer on survivality of lambs in the Ethiopian highland sheeThe influence of passively acquired immunity on neonatal lamb mortality was studied at Debre Berhan station, International Livestock Center for Africa (ILCA) during July 1989 to December 1990. Samples and data were collected from 628 sheep of 540, 32 and 56 Menz, Wollo and Horro breeds, respectively. Information were also obtained on lamb birth, lamb survival upto 1 month of age, on dam and environment. Comparison between the relationship of Ig levels and mortality rates of those lambs with failure, partial and adequate transfers of Ig were made using Chi-square test.